Severe acute respiratory syndrome coronavirus-2 seroprevalence in non-vaccinated people living with HIV in Uganda during 2022 - Ainembabazi, Provia; Najjemba, Letisha; Musaazi, Joseph; Hönemann, Mario; Castelnuovo, Barbara; von Braun, Amrei (Frontiers in Virology, 2024)
A cross-sectional study on severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) seroprevalence among unvaccinated people living with HIV (PLWH) was conducted in Kampala, Uganda, in 2022. Data collection was done using a structured questionnaire. SARS-CoV-2 serologies were done using the Roche Elecsys Anti-SARS-CoV-2 S immunoassay, which assesses the adaptive humoral immune response to the SARS-CoV-2 Spike protein. A total of 575 PLWH (female n=355, 61.7%) with a median age of 49 years (IQR 39-55) were included. SARS-CoV-2 seroprevalence was 93%. The majority had antibody concentration levels ≥ 250 U/ml (n=383, 66.6%). Participants aged >55 years were significantly more likely to have lower antibody concentrations compared to younger participants (p-value < 0.001). A high BMI (≥ 30 kg/m2) was significantly associated with higher antibody concentrations (p-value 0.001). Concerning COVID-19 history, a small proportion of participants (n=79, 13.6%) reported contact with a known COVID-19 patient. Only 8.1% (n=47) had ever had a nasopharyngeal swab for SARS-CoV-2 RT-PCR done, and 3.1% (n=18) actually had a laboratory-confirmed SARS-CoV-2 infection in the past. SARS-CoV-2 seroprevalence was high among our study population, which may be attributed to the fact that the study took place right after all restrictions were lifted and the population was exposed to the dominant Omicron variant. Interestingly, only a small proportion of infections had been laboratory-confirmed.